Metodologia para eficientização do processo de elaboração e análise de projetos de linhas aéreas rurais de distribuição de energia elétrica - Ribeiro, Cássio Landim (2017)
This paper presents a new methodology aimed at increasing efficiency in the dimensioning and approval stage of aerial rural electricity distribution lines projects. As a substitute for the sequential process currently employed, the approach proposed here is based on Simultaneous Engineering, where all the actors of the process have access to the computational tool, in a web platform, that allows implementing the methodology, enabling the multidisciplinary activity to be carried out in a parallel way. The estimates gathered indicate that the tool will allow the reduction of the time spent for the elaboration and approval of the projects, allowing: to reduce the total cost in man-hour spent by the electric utility; satisfy the customer's needs more quickly; optimize the mechanical dimensioning of distribution lines; and provide additional financial gain to the concessionaire due to the reduction of the average time to effectively start supplying electric power.